Long-run Social and Economic Responses of Fertility in the United States (The Pakistan Development Review, 1988)
Based on the results of an econometric analysis, the paper looks into the dynamic response of fertility behaviour in the United States, to changes in some of its determinants. Specifically, the effect of current and past marriage rates on fertility has been studied. In doing so, the role of permanent income and the divorce rate on the marriage rate, and through it, on fertility, has also been examined.